Magnetic resonance-guided focused ultrasound unilateral thalamotomy for medically refractory essential tremor: 3-year follow-up data - Tamburin, Stefano; Paio, Fabio; Bovi, Tommaso; Bulgarelli, Giorgia; Longhi, Michele; Foroni, Roberto; Mantovani, Elisa; Polloniato, Paolo Maria; Tagliamonte, Micaela; Zivelonghi, Emanuele; Zucchella, Chiara; Cavedon, Carlo; et al. (Frontiers in Neurology, 2024)
Introduction Magnetic resonance–guided focused ultrasound (MRgFUS) thalamotomy of the ventralis intermediate (Vim) nucleus is an “incisionless” treatment for medically refractory essential tremor (ET). We present data on 49 consecutive cases of MRgFUS Vim thalamotomy followed-up for 3 years and review the literature on studies with longer follow-up data. Methods A retrospective chart review of patients who underwent MRgFUS thalamotomy (January 2018–December 2020) at our institution was performed. Clinical Rating Scale for Tremor (CRST) and Quality of Life in Essential Tremor (QUEST) scores were obtained pre-operatively and at each follow-up with an assessment of side effects. Patients had post-operative magnetic resonance imaging within 24 h and at 1 month to figure out lesion location, size, and extent. The results of studies with follow-up ≥3 years were summarized through a literature review. Results The CRST total (baseline: 58.6 ± 17.1, 3-year: 40.8 ± 18.0) and subscale scores (A + B, baseline: 23.5 ± 6.3, 3-year: 12.8 ± 7.9; C, baseline: 12.7 ± 4.3, 3-year: 5.8 ± 3.9) and the QUEST score (baseline: 38.0 ± 14.8, 3-year: 18.7 ± 13.3) showed significant improvement that was stable during the 3-year follow-up. Three patients reported tremor recurrence and two were satisfactorily retreated. Side effects were reported by 44% of patients (severe: 4%, mild and transient: 40%). The improvement in tremor and quality of life in our cohort was consistent with the literature. Conclusion We confirmed the effectiveness and safety of MRgFUS Vim thalamotomy in medically refractory ET up to 3 years.